Case Discussion and Literature Review: Cancer Immunotherapy, Severe Immune-Related Adverse Events, Multi-Inflammatory Syndrome, and Severe Acute Respiratory Syndrome Coronavirus 2 - Ragoonanan, Dristhi; Khazal, Sajad J.; Mejia, Rodrigo; Ewing, Linette; Durand, Jean-Bernard; Bashoura, Lara; Tayar, Jean; Dailey Garnes, Natalie; Petropoulos, Demetrios; Tewari, Priti; Bhatti, Micah; Ahmad, Ali Haider; et al. (Frontiers in Oncology, 2021)
Pediatric, adolescent and young adult (AYA) patients receiving novel cancer immunotherapies may develop associated toxicities with overlapping signs and symptoms, that are not always easily distinguished from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection/clinical sequelae. We describe 2 diagnostically challenging cases of SARS-CoV-2 and Multi-Inflammatory Syndrome-Adult (MIS-A), in patients with a history of acute lymphoblastic leukemia following cellular therapy administration and review evolving characterization of both the natural course of SARS-CoV-2 infection and toxicities experienced in younger cancer immunotherapy patients. Vigilant monitoring for unique presentations and epidemiologic surveillance to promptly detect changes in incidence of either condition may be warranted.